2009
DOI: 10.2202/1469-3569.1271
|View full text |Cite
|
Sign up to set email alerts
|

Walmart and Values: Painting the Town Red?

Abstract: This essay explores the relationship between commerce and culture in the context of the recent debate over the social effect of Wal-Mart. In spite of much public debate, little is known about how Wal-Mart affects values. Using data collected from multiple sources, we show there is little evidence that Wal-Mart makes communities more conservative or more progressive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…However, Sobel and Dean (2008) found that Walmart has not had a long-run impact on the overall size and profitability of the small business sector in the United States, suggesting that the increase in poverty (if it exists) may come from other sectors. Other studies have looked at the impact Walmart has had on body mass index (Courtemanche and Carden 2011), social capital (Goetz andRupasingha 2006, Carden, Courtemanche andMeiners 2009a), leisure activities (Carden and Courtemanche 2009) and traditional values (Carden, Courtemanche and Meiners 2009b).…”
Section: Literaturementioning
confidence: 99%
“…However, Sobel and Dean (2008) found that Walmart has not had a long-run impact on the overall size and profitability of the small business sector in the United States, suggesting that the increase in poverty (if it exists) may come from other sectors. Other studies have looked at the impact Walmart has had on body mass index (Courtemanche and Carden 2011), social capital (Goetz andRupasingha 2006, Carden, Courtemanche andMeiners 2009a), leisure activities (Carden and Courtemanche 2009) and traditional values (Carden, Courtemanche and Meiners 2009b).…”
Section: Literaturementioning
confidence: 99%
“…The authors attributed these results to a general withdrawal of individuals affected by the arrival of the chain, or greater apathy. Carden, Courtemanche, and Meiners (2009a, 2009b) reexamine the hypotheses tested by Goetz and Rupasingha and focus on the effect of WalMart on social capital–related factors such as membership in clubs, religious participation, and time spent with friends, using Census data as well as the DDB Needham Lifestyle survey, which was also used by Putnam (2000). They conclude that there is no robust or consistent WalMart effect on social capital: some measures are being positively affected, whereas others decline.…”
Section: The Walmart Effectmentioning
confidence: 99%
“…Goetz and Rupasingha () find empirically that Wal‐Mart has an independent effect on various civic activities in counties, whereas Carden, Courtemanche, and Meiners () find more equivocal effects of Wal‐Mart on local culture and social capital.…”
mentioning
confidence: 99%